THE EFFECTS OF r-HDPE/r-PP FORMULATION RATIO INTO MECHANICAL, THERMAL AND MORPHOLOGICAL BEHAVIOR OF r-HDPE/r-PP POLYMERIC BLENDS - Razak, Jeefferie Bin; Wahid, Siti Zaleha; Mohamad, Noraiham; Puspitasari, Poppy; Jaafar, Rosidah; Tutuko, Pindo (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2020)
This study has reported the effects of different formulation ratio between recycled high density polyethylene (r-HDPE) and recycled polypropylene (r-PP) into the resulted mechanical, thermal and morphological properties of r-HDPE/r-PP polymeric blends. About five (5) different formulation ratio of r-HDPE/r-PP have been prepared and tested. The best combination ratio between r-HDPE and r-PP was determined in this work. It was found that the 70/30 wt.% of r-HDPE/r-PP blend possessed an outstanding mechanical and physical strength. About 59.80% and 2.30% of positive improvement in comparison to 0/100 wt.% of r-HDPE/r-PP was achieved for both of tensile strength and hardness, respectively. Interestingly, for 70/30 wt.% of r-HDPE/r-PP blend had also experienced major increased in their elongation at break up to 473%. The fracture morphological behavior of the tested samples that were observed via SEM observation, had established the interaction between the structure and properties of produced r-HDPE/r-PP blends, especially on the miscibility state between the r-HDPE and r-PP phases. Thermal evaluation by using the DSC had confirmed the partial miscibility state due to dominant peak shifting at 120 - 140Â°C and obvious melting peak reduction pattern. Overall, from this study, it was found that the blending between r-HDPE and r-PP into r-HDPE/r-PP blends are feasible to improve the properties of primary phase.